Teacher's Strategies to Encourage Students to Speak English in the Class at SMPN 5 Banjarbaru - Rahmawati; Nana Suciati; Tri Winindyasari Palupi (Lentera: Jurnal Ilmiah Kependidikan, 2023)
The teacher's strategy includes various actions or steps taken by the teacher to solve problems and achieve learning goals. In this study, researchers examined how the teacher's strategy in encouraging students to be more confident in speaking English. This study aimed to describe the teacher's strategy in encouraging students to speak English in class at SMPN 5 Banjarbaru. This was a qualitative study with data collected from one teacher and two students of class VII of SMPN 5 Banjarbaru. This study uses a closed questionnaire in data collection, and the results of the questionnaire will be presented in a qualitative descriptive form. This questionnaire is used to find out the teacher's strategy in encouraging students to speak English in class. Data analysis was carried out through data condensation, data display, and drawing verification conclusions. The results of this study indicate that teachers use 3 strategies to encourage class VII students of SMPN 5 Banjarbaru to speak English in class, namely; Story Completion, Role Play, and Simulation. In each strategy there are activities used by the teacher, this activity aims to support the strategies used by the teacher. The activities used by the teacher are based on Speaking Activities and the principles of teaching English speaking.